2018
DOI: 10.1002/pbc.27520
|View full text |Cite
|
Sign up to set email alerts
|

Malignant peripheral nerve sheath tumor: Transformation in a patient with neurofibromatosis type 2

Abstract: Malignant peripheral nerve sheath tumor (MPNST) is a rare soft‐tissue sarcoma with an unfavorable prognosis and limited therapeutic options. MPNSTs can be sporadic, but are often associated with neurofibromatosis (NF) 1 and usually arise from preexisting neurofibromas. MPNSTs in patients with NF2 have been reported in only exceedingly rare cases, and the mechanisms underlying transformation into an MPNST have not been fully elucidated. Here, we describe the clinicopathological and genomic features of a periphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“… 3 Despite maximal aggressive treatment, prognosis is unfavorable and metastases to the spine are common. 1 , 3 , 8 Carlson et al reported a 54% mortality rate due to disease progression at a median of 3 months following diagnosis in their series. 1 …”
Section: Discussionmentioning
confidence: 94%
“… 3 Despite maximal aggressive treatment, prognosis is unfavorable and metastases to the spine are common. 1 , 3 , 8 Carlson et al reported a 54% mortality rate due to disease progression at a median of 3 months following diagnosis in their series. 1 …”
Section: Discussionmentioning
confidence: 94%
“…Of note, we did not observe any case of malignant peripheral nerve sheath tumor. The association between NF2 and malignant peripheral nerve sheath tumor remains controversial, with only 1 case reported in peripheral nerves 33 and none in a large series of nonirradiated vestibular tumors. 34 In a series of PNS in patients with NF2, authors have reported a higher rate of preoperative motor (26%) and sensory (20%) loss compared with sporadic cases 35 and suggested that this observation might be due to a delay in the surgery of peripheral nerve lesion because of the priority given to the management of central lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, we did not observe any case of malignant peripheral nerve sheath tumor. The association between NF2 and malignant peripheral nerve sheath tumor remains controversial, with only 1 case reported in peripheral nerves 33 and none in a large series of nonirradiated vestibular tumors. 34…”
Section: Discussionmentioning
confidence: 99%
“…In some cancers, the loss of NF2, an upstream negative regulator of HIPPO signaling, simultaneously unleashed YAP/ TAZ and SMAD2/3 activation leading indirectly to the induction of aerobic glycolysis via derepression of GLUT, HK2, LDH and MCT genes [121]. Interestingly, NF2 mutations might contribute to the maintenance of rare aggressive sarcomas [122]. This hypothesis was tested in a kidney cancer cell model bearing NF2 mutations [123].…”
Section: An Altered Hippo Pathway Induces Aerobic Glycolysis In Stsmentioning
confidence: 99%